Analysis of Physics Education Students' Difficulties in Electricity and Magnetic Concepts in The Covid-19 Pandemic - Amiruddin Kade*; Supriyatman Supriyatman; Darsikin Darsikin; Muhammad Zaky (Jurnal Pendidikan Sains Indonesia, 2022)
This research is based on the behavior of students who are confused about explaining a natural phenomenon when taking electricity and magnetism courses. The covid-19 pandemic, which requires online courses, adds to the problems in improving the quality of learning in electricity and magnetism courses. As prospective teachers, physics education students with low concept mastery are certainly very concerned because they will teach it to their students. So this research aims to identify difficulties and recommendations for learning electricity and magnetism. The qualitative descriptive method is used to obtain a description of the problem, and obtain recommendations for effective and efficient learning. Learning is done online through zoom meetings and LMS.fkip.untad.ac.id. Data was collected by testing the mastery of the concept of electricity and magnetism. The test was given online to 40 students and interviews with 5 students as respondents. The results showed that the biggest difficulty of students in applying the concept of the potential vector was about 70%, analysis on the application of Ampere's law was about 47.5%, applying the concept of the field in a cylinder about 30%, and applying the Biot-Savart law was about 25%. It can be concluded that there are still many students who have difficulty mastering the concepts of electricity and magnetism after participating in online learning